KENIKMATAN IRONIS BAGI MANTAN PREMAN DI YOGYAKARTA SETELAH MENONTON SINETRON PREMAN PENSIUN - Yul Rachmawati; Tangguh Okta Wibowo (Jurusan Ilmu Komunikasi UTM, 2018)
ABSTRACTThis study attempts to explore how the reception of the audiences after watching Preman Pensiun (PP) soap opera, a comedy soap opera by Aris Nugraha which has aired up to three series. The problematization of this study comes when PP soap opera raises a question, how do audiences’response in the city other than Bandung? This study tries to understand how receptive thugs who are retired or ex-thugs after watched PP soap operas in their daily lives. For data collection, researchers conducted in-depth interviews after approaching three informants as former thugs in Yogyakarta. The result of this study is the communication of former thugs in daily life after they have constructed and reproduced values adopted from PP soap opera. Last, PP soap opera gives pleasure for the ex-thugs in providing entertainment, but also it gives ironic pleasure and paradoxwhen they feel away with the pleasure.